Effect of Heat Waves on Some Italian Brown Swiss Dairy Cows' Production Patterns - Maggiolino, Aristide; Landi, Vincenzo; Bartolomeo, Nicola; Bernabucci, Umberto; Santus, Enrico; Bragaglio, Andrea; De Palo, Pasquale (Frontiers in Animal Science, 2022)
Climate change is worldwide impacting efficiency and welfare standards in livestock production systems. Considering the sensibility to heat stress reported for different milk production patterns in Italian Brown Swiss, this study aims to evaluate the effect of heat waves of different length on some milk production traits (fat-corrected milk, energy corrected milk, protein and fat yield, protein percentage, cheese production at 24h and cheese yield). A 10-year data set (2009–2018), containing 202,776 test-day records from 23,296 Brown Swiss cows was used. The dataset was merged both with the daily maximum THI recorded by weather stations and with the daily maximum THI threshold for each trait in Italian Brown Swiss cows. The study considered 4 different heat waves according to their length: two, three, four and five consecutive days before the test-day over the weighted THI threshold. Milk production traits were determined as the difference in losses compared to those after only one day before the test day over the weighted maximum THI. All traits showed to be affected by heat waves. Particularly, protein percentage losses increased from -0.047% to -0.070% after 2 consecutive days over the daily THI threshold, reaching -0.10% to -0.14% after 5 days (P < 0.01), showing a worsening trend with the increasing length of heat waves. First parity cows showed to be more sensitive to heat waves than other parity classes, recording greater losses after shorter heatwaves, compared to multiparous cows, for protein yield and, consequently, for cheese production at 24h. This suggests less efficient metabolic response to heat stress and exposure time in primiparous, compared to multiparous cows, probably due to their incomplete growth process that overlap milk production, making more difficult for them to dissipate heat. Although actions to mitigate heat stress are always needed in livestock, this study points out that often time exposure to warm periods worsen milk production traits in Brown Swiss cows.